H-Configuration Modular Rotor PMFSM for Passenger Drone - Mostaman, Nur Afiqah; Jenal, Mahyuzie; Sulaiman, Erwan; Naufal, Syed Muhammad (Multidisciplinary Applied Research and Innovation, 2022)
Currently, Brushless DC (BLDC) outer rotor permanent magnet motor has been applied in courier drone. This structure makes the motor less robust at high speed as well as mechanically weak. To resolve the issue, an optimization of double stator with H-design modular rotor permanent magnet PMFSM with unique features of non-overlap winding, low copper losses, high efficiency, a smaller number of permanent magnet (PM) has been proposed. The optimization based on Local Optimization Method (LOM) has been used. The project aims to ensure that the passenger drone motor designed able to show the improvement on high torque and better performances motor. In addition, the methodology of this study has been carried out in detail in order to complete and simplify the process of data collection in a more structured and ordered method by using JMAG-Designer version 16.0 software. Hence,the results for this design have been observed under no-load and load condition which shows that it is suitable with the passenger drone with modular rotor motor torque which is 46.13 Nm.